Momentum Returns and Transaction Costs in the U.K. Stock Market - Wang, Xiaopeng (2010)
This paper evaluates the existence of momentum profits based on the U.K. stock market, by taking into account the transaction costs. It concludes that momentum strategy is profitable in normal cases and transaction costs can only partly explain the momentum return. The research is conducted by forming momentum portfolios with six-month holding period and twelve-month holding period respectively based on the ranking of the previous six-month accumulative stock returns. The estimation of transaction costs is conducted by quoted spread method and effective spread method. From the observations, it is found that the performance of the winner portfolios outperform that of the loser ones. Transaction costs are not that significant as stated in prior literatures because it is not high enough to offset all momentum profits. Furthermore, it is suggested that the probability of the momentum strategy is also affected by other factors like systematic risk.